GOING CONCERN AUDIT OPINION: IS IT AFFECTED BY BUSINESS RISK AND INTERNAL CONTROL? - Mulyana, Dendi; Widarsono, Agus; Apandi, R. Nelly Nur (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2023)
The auditor issues a going concern audit opinion based on concerns about the future viability of a company's operations that may be influenced by external responses. The objective of this study is to investigate the impact of business risk, comprising firm size, leverage, and mass media coverage, as well as company internal control, which comprises training activities and internal auditors, on the going concern audit opinion. The research was carried out on 111 companies listed on the IDX's special surveillance board as a sample. In this study, quantitative methodologies with descriptive and causal methods are implemented. Hypothesis testing using logistical regression analysis. The results show that leverage and mass media coverage respectively have a positive influence on the going concern audit opinion, whereas the firm size, training activities, and internal auditor respectively have no influence on the going concern audit opinion.